PERSEPSI PEMBACA TERHADAP PEMBERITAAN “MK TOLAK LEGALISASI GANJA MEDIS UNTUK KESEHATAN!” DI PORTAL BERITA DETIKCOM - Ramadhan Sigih Pratama; Tiara Puspanidra; Ratih Siti Aminah (Jurnal Penelitian Sosial Ilmu Komunikasi, 2023)
We already know that technology has become more sophisticated over time, resulting in progress and novelty in many sectors, the mass media industry being one of them. Technological developments have not failed to influence the world of journalism today, the mass media industry is increasingly sophisticated and has easy access for readers, so that news from abroad can be easily read by Indonesian people today. For example, news about the legalization of marijuana in Thailand has sparked discussion in Indonesia, so researchers want to conduct research on readers' perceptions regarding news about the rejection of legalization of marijuana in Indonesia. This research aims to find out how the news is exposed, what is the perception of the news "MK Rejects Legalization of Medical Marijuana for Health!" on the detikcom news portal, and what is the relationship between news exposure and readers' perceptions of the news "MK Rejects Legalization of Medical Marijuana for Health!" on the detikcom news portal. This research uses one independent variable, namely news exposure (X) and the indicators used to describe this variable are frequency, duration and content of news. One dependent variable is the perception of the news about the Constitutional Court rejecting the legalization of medical marijuana for health (Y) and the indicators used to describe this variable are sensation, attention and interpretation. This research was conducted on Instagram @detikcom in November 2022. This research used descriptive-correlational quantitative research methods. The population used was Instagram followers @detikcom and the sample used was 100 respondents who were followers of the Instagram account @detikcom. The data collection technique used was by distributing questionnaires to respondents. The data analysis technique used is descriptive statistical analysis (Rank Spearman). The subjects in this research were followers of the Instagram account @detikcom, while the objects in this research were the researchers highlighting the news "MK Rejects Legalization of Medical Marijuana for Health!" which was published on the Detik.com news portal on July 20 2022. The results of the research show that there is a relationship between variable X and variable Y seen from the coefficient value of 0.679 which is included in the strong category, with a significance value of 0.000.